Pendampingan Masyarakat Kelurahan Pangkalan Jati Mengenai Dampak Hukum Penolakan Vaksinasi di Masa Pandemi Covid-19 - Dwi Desi Yayi Tarina; Rianda Dirkareshza; Kristina Simbolon; Rosalia Dika Agustanti (Universitas Mathla'ul Anwar Banten, 2021)
COMMUNITY ASSISTANCE IN PANGKALAN JATI VILLAGE REGARDING THE LEGAL IMPACT OF REFUSAL TO VACCINATION DURING THE COVID-19 PANDEMIC. Law of the Republic of Indonesia No. 36 of 2009 on Health, confirms that the government requires immunization and has an important role in maintaining public health, one of the efforts made by the provision of vaccines. In relation to this, people become afraid and even refuse to be vaccinated. As for some hoaxes that are spread is injections of vaccines in men must be in the penis, covid-19 vaccine can engineer genetics, die, exterminate the indigenous population, contain vero cells from african green monkeys and only Indonesia ordered the Covid-19 vaccine. This is the basis of the community's assistance, because of the many fake news (Hoaxes) that are spread massively. The news is spread through whatsapp group, facebook and various other applications. The method used in the implementation of worship in this society is a combination of community educationand dialogue. Community service activities are carried out starting from the stage of preparation, implementation and evaluation. The target of this service activity is the community of Pangkalan Jati Village, Depok City. Where a number of these communities began to be affected by hoaxes about the negatives of the Covid-19 vaccine. The survey in Pangkalan Jati Village Community Assistance on the Impact of Vaccination Rejection Law during the Covid 19 Pandemic showed that participants' understanding of the legal impact of vaccination rejection touched a perfect figure of 100%. As well as other surveys showed that the willingness of participants to follow vaccination was 92.3%. This survey aims to be an indicator of the success or understanding of each participant present on the day.